Oxidation kinetics of Cr-coated zirconium alloy: Effect of coating thickness and microstructure. (October 2020) - Kashkarov, E.B.; Sidelev, D.V.; Syrtanov, M.S.; Tang, C.; Steinbrück, M.
Highlights: Zr-1Nb alloy coated by dense Cr exhibits better oxidation performance. Transition time into non-protective behavior increases with coating thickness. Inter-diffusion of Cr and Zr significantly affects the oxidation kinetics. Abstract: Cr coatings with the thickness of 4.5–9.0 μm and dense/columnar microstructure were deposited onto Zr alloy by cooled or hot target magnetron sputtering. Steam oxidation tests were performed under temperature ramp from 500 to 1200 °C and isothermal treatment at 900−1200 °C for 10−30 min. The measurements of mass gain showed different oxidation kinetics depending on microstructure and thickness of the as-deposited Cr coatings. The dense microstructure is favorable to prevent alloy oxidation as long as the Cr layer is intact. The higher activation energy of 202 kJ/mol is observed for the dense 4.5 μm-thick Cr coating while thicker columnar coatings have 177−183 kJ/mol. The time of transition from protective to non-protective behavior increases with coating thickness. It was shown that the 9 μm-thick Cr coating with columnar microstructure better protects the zirconium alloy from oxidation at 1200 °C for 10 min in comparison with thinner coatings. The fast inter-diffusion of Cr and Zr at coating/alloy interface significantly affects the oxidation kinetics of Cr-coated zirconium alloy at temperatures above 1100 °C and long oxidation time.